On Relative Soft Set (International Journal of Scientific Research and Management (IJSRM), 2013)
Molodtsov in 1999 introduced the concept of soft set theory which can be used as a general mathematical tool for dealing with uncertainties about vague concepts. In this paper, we recall the definition of soft set, its properties and operations. We introduce the definition of relative soft set, its basic properties and operations such as union, intersection and complement. We give relevant examples for these concepts.Basic properties of the operations are also given.